Implementation of SARG04 decoy state quantum key distribution - Sellami , Ali; Mahmoud, Omer (2011)
The experiment of decoy state QKD has been reported using commercial QKD system based on a standard bi-directional ‘Plug & Play’ set-up. By making simple modifications to a commercial quantum key distribution system, decoy state QKD allows us to achieve much better performance than QKD system without decoy state in terms of key generation rate and distance. One decoy state protocol has been implemented. The obtained results demonstrate an unconditionally secure key rate of 0.127 x 10-4 per pulse for a 10 km fiber length.